PENGARUH SUASANA CAFE DAN HARGA TERHADAP KEPUASAN PELANGGAN DI MARALOKA CAFE CIANJUR - Siti Faoziah; Agung Pramudya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the competition of café businesses in Cianjur, where the atmosphere of the café and the price of the product are important factors that affect customer satisfaction. Cafe Maraloka Cianjur takes advantage of the comfort of the atmosphere and the right pricing to attract and retain customers. The purpose of this study is to determine the influence of café atmosphere and price on customer satisfaction. The research uses quantitative methods with a descriptive and verifiable approach. Data collection was carried out through the distribution of questionnaires to as many as 90 respondents, using probability sampling techniques. Data analysis was carried out by validity test, reliability test, classical assumption test, multiple linear regression analysis, t test and F test using the SPSS 25 application. The results of the study show that the atmosphere of the café and the price have a positive and significant effect on customer satisfaction, both partially and simultaneously. Thus, improving the quality of the atmosphere and the corresponding price can drive customer satisfaction and loyalty.